Assistance and Management of E-Commerce and Digital Marketing in Pujon Kidul Tourism Village - Iqbal Ramadhani Fuadiputra; Fauzik Lendriyono; Titiek Ambarwati (Kontribusia : Research Dissemination for Community Development, 2022)
In this service program, the devotees try to respond to issues related to the development carried out by the Pujon Kidul tourist village, especially in increasing merchandise sales and introducing several new tourist destinations in Pujon Kidul. Because of the information obtained, the trend is also increasingly erratic during a pandemic like today. This has encouraged the service team to provide some touch of technology, especially in marketing. Through the digital marketing and e-commerce development program, our community service team hopes that with this program, the community will experience an increase both in terms of income and visits to tourist attractions that are running now. This program hopes that it will also introduce potential outside of Café Sawah, owned by Pujon Kidul. This program is also appropriate because, during a pandemic like this, a decrease in the number of visitors has also been experienced in Pujon Kidul. With the introduction of other potential villages, it is hoped that the attractiveness and capacity accommodated will be in the Rice Field Café and different potentials. The method used in this service process is to use digital marketing and e-commerce as a solution to increase visits and sales of products owned by BUMdes Pujon Kidul. Social media is one of the media used to increase interest and visits to the tourist village of Pujon Kidul. Measuring success can be calculated from direct visits to tourist attractions and visits to Pujon Kidul's social media. Based on the results of visits from both social media and tourist attractions, there has been an increase for followers at 11,800, and for holidays, there has been an increase to 6500 tourists visiting. The results of e-commerce and digital marketing training are expected to provide other income regularly for citizens who depend on their life from Pujon Kidul tourism.